The Effectiveness of Dance Learning on Locomotor Movement Skills Development Children Aged 5-6 Years in PAUD Sekar Nagari - Rahmadani, Ni Kadek Aris; Tasuah, Neneng (Indonesian Journal of Early Childhood Education Studies, 2019)
Locomotor movement skills can be developed through many ways, one of them with dance learning. The form of dance learning is music and movement because the children can do the dance according to the music and song lyrics. Locomotor skill is are movements that require the body to move in space. Locomotor movement skills in this dance include running, stepping and jumping. Type of research method used quantitative research using experiment, pre-experimental design, namely one group pretest-posttest. This research giving treatment and examining the assessment from before and after the treatment. This study aims at observing to develop of locomotor movement skills of 5-6 years old with dance learning. Indicate that increase in locomotor movement skills of children with dance learning, the score of pretest-postest. After the research is conducted, the result obtained is grades of locomotor movement skills of children in dance learning in early childhood Sekar Nagari. Through the music and movement dance learning, it is expected that children can improve the aspect of locomotor movement skills using motions and song of â€œdua mata sayaâ€, because the dance is simple and every children can do this dance with memorize the song lyrics to move their body.